Congenital giant dermoid cyst of the orbit associated with microphthalmia and cataract (1995)
A case of a giant dermoid cyst of the orbit associated with microphthalmia in a two-year old female child is reported. Clinical diagnosis of the condition was made when the child was two months old, although it had been observed at birth by the parents. Surgical excision of the tumour and the microphthalmic eye was undertaken when the child was two years old. Findings at the operation included a giant cyst that was partially intraorbital with a portion of it extending into the temporal fossa, a microphthalmic eye with cataract and non-closure of the zygomatico-frontal suture. Six months after surgery, there was no evidence of recurrence of the tumour.